Cold chain logistics: an impediment in the perishable food industry of India. (2018) - Singh, Binod Kumar; Negi, Saurav
Indian agriculture sector plays a significant role in the Indian economy by contributing 17.9% of GDP. Fruits and vegetables sector play an important role in the Indian agriculture sector which is suffering from huge post-harvest losses due to improper cold chain logistics. This study gives an insight of post harvest losses and its linkage with cold chain logistics in India. This paper discussed the challenges of cold chain industry in India, cold chain gap assessment, and post-harvest losses due to inadequate cold chain. SCOPE Situational analysis, PESTEL analysis and SWOT analysis is conducted in detail, which revealed that cold chain industry is facing various challenges like high cost of investments, energy requirements, poor visibility of the products in transit, uneven distribution of cold chain capacities, and obsolete technology. Further, this study is also able to draw a roadmap that can be used by stakeholders and policy makers in this sector to minimise post-harvest losses.